Pembentukkan Nilai Ketawadhu’an Santri Melalui Penyebaran Stiker UW: Di Pondok Pesantren Putra Al Urwatul Wutsqo Jombang - Moh. Kholik; Mar'atul Azizah; Muhammad Ramadhan (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2020)
This research describes the implementation of stickers distribution in forming students' humble at al Urwatul Wutsqo Islamic Boarding School, Jombang. This research is qualitative research, data collected through interviews, observation and documentation. The data then analyzed by Miles and Huberman model such as, reduction, display and verification data. The results of this study are the distribution of stickers is carried out at least twice a year, during semester holidays and the boarder orders from, the distribution of stickers to maintain the existence of the Islamic boarding school, inviting others to look for knowledge at al Urwatul Wutsqo Islamic boarding school, for boarding, studying, training students to be better humble either to Allah, to religion, to prophet to theologian, and to their peers. The students are also given guidance in distributing stickers, as a means of practicing the prophet nature in seeking people and spreading the religion of Allah. The technic of distribution are the students have stickers and all schools destination data that will be given. Then, the students come to the school to see the principal or representative to get out recommendations; the next, students distribute the stickers.